Reflections on Political Theory - Wood, N. author. aut Link
X, 178 p.
Keywords: In this thought-provoking study, Neal Wood challenges the conception of political theory as a lofty discipline remote from the world of real politics. Drawing on the examples of thinkers from Plato to those of the nineteenth century, he attempts to define political theory by examining the nature of the state and politics, by identifying the major characteristics that their theories share and by analyzing the conditions that have favoured their creation. Wood critically explores the two principle approaches to studying the work of past theorists - the philosophical and historical - and evaluates the relevance of Marxism. The various theories are not treated as blueprints but collectively as a voice of reason from the past, which can inspire and guide present and future theorizing.